The Relationships Among Childhood Maltreatment, Emotion Regulation, and Sexual Risk-Taking in Men from Urban STD Clinics - Mueller, Tiffany M. (J Aggress Maltreat Trauma, 2012)
This study sought to examine the relationships among emotion regulation difficulties, childhood maltreatment, and risky sexual behavior in a sample of 320 heterosexual men recruited from urban STD clinics. Overall childhood maltreatment and several specific types of child abuse were significantly associated with emotion dysregulation, number of sexual partners, and STI diagnosis. There was evidence of an additive effect of multiple forms of maltreatment on difficulties with emotion regulation and sexual risk-taking. Impulse control difficulties and access to emotion regulation strategies, two components of emotion dysregulation, were related to measures of risky sexual behavior. Furthermore, limited access to emotion regulation strategies mediated the relationship between frequency of childhood sexual abuse and a greater number of lifetime sexual partners. This study has important implications for developing effective interventions to reduce the spread of STI’s and HIV by expanding affect regulation and distress tolerance strategies among men who have experienced childhood maltreatment.